Formação de professores em projetos interdisciplinares em aprendizagem ativa : relato de caso - Leite, Fernanda Fernandes (My University, 2017)
The recent study, which is part of the Research Fundamentals and Educational Strategies in Science and Mathematics Teaching, concerns the qualification of teachers in interdisciplinary projects of active learning at the General Osório Municipal School / Vacaria (RS). From a perspective of democratic management, activities were carried out involving the students, families of the students, management team and teachers of the School to implement an interdisciplinary project, to solve the problem of excessive spending of electricity in school. The general objective of this qualitative research was to enable teachers to develop an interdisciplinary, sustainable and contextualized proposal of active learning using the PBL methodology, in order to address the themes of energy production and consumption. This work had as theoretical support researchers who contributed to the structuring of a teaching proposal with projects that lead to the change of habits, attitudes and reflection on the pedagogical practice itself, highlighting the contributions of Freire, which emphasizes the need to transform the present to face the future. The research was significant because it enabled the teachers to review their pedagogical practices, as well as to strengthen a joint work, seeking the full development of the students. Because of the teachers' action, the students developed autonomy, critical sense and conscious attitudes in the face of problematizing teaching, so that the proposed problem allowed for changes in habits and attitudes, aiming at sustainability. The results of this research were only possible because they had a group of professionals committed as the training and who accepted the challenge of working together.
O presente estudo inserido na linha de Pesquisa Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática, diz respeito à formação de professores em projetos interdisciplinares de aprendizagem ativa da Escola Municipal de Ensino Fundamental General Osório de Vacaria (RS). Numa perspectiva de gestão democrática, foram realizaram atividades envolvendo os alunos, familiares dos educandos, equipe gestora e professores da Escola para implementação de um projeto interdisciplinar, para resolução do problema de gasto excessivo de energia elétrica na escola.O objetivo geral desta pesquisa qualitativa foi capacitar os professores a desenvolver uma proposta interdisciplinar, sustentável e contextualizada de aprendizagem ativa utilizando a metodologia PBL, a fim de abordar as temáticas de produção e consumo de energia. Este trabalho teve como suporte teórico pesquisadores que contribuíram para estruturação de uma proposta de ensino com projetos que levasse à mudança de hábitos, atitudes e reflexão sobre a própria prática pedagógica, destacando-se as contribuições de Freire, que enfatiza a necessidade de transformar o presente para enfrentar o futuro. A pesquisa apresentou-se significativa por viabilizar que os professores revissem suas práticas pedagógicas, além de fortalecer um trabalho conjunto, buscando o desenvolvimento pleno dos educandos. Em consequência da ação dos professores, os alunos desenvolveram autonomia, senso crítico e atitudes conscientes, diante de um ensino problematizador, de modo que o problema proposto possibilitou mudanças de hábitos e atitudes, visando a sustentabilidade. Os resultados desta pesquisa só foram possíveis por ter um grupo de profissionais comprometidos como a capacitação e que aceitaram odesafio de trabalhar em conjunto.
Keywords: Professores - Formação; Aprendizagem; Sustentabilidade; Teachers, Training of; Learning; Sustainability